2021
DOI: 10.3390/f12020215
|View full text |Cite
|
Sign up to set email alerts
|

Root Foraging Ability for Phosphorus in Different Genotypes Taxodium ‘Zhongshanshan’ and Their Parents under Phosphorus Deficiency

Abstract: The phosphorus (P) deficiency is the one of the key constraints for Taxodium ‘Zhongshanshan’ afforestation. A hydroponic experiment was conducted to explore root foraging ability for P in different genotypes of Taxodium ‘Zhongshanshan’ (T.’Zhongshanshan’) and their parents (T.mucronatum and T.distichum). Five P levels of CK (31 mg/L), P15 (15 mg/L), P10 (10 mg/L), P5 (5 mg/L), and P0 (0 mg/L) were set up as the P deficiency stress treatment. The plant P contents, root morphological indices, and plant growth tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The total dry weight of cotton reduced by 70.04 and 77.26% in the ND and JM cultivars, respectively, under low P stress, compared with PR conditions. These findings are consistent with the results of Xie et al (2021), who found that low P stress can significantly reduce the dry weight of cedar trees.…”
Section: Low P Stress Reduces Cotton Dry Matter Weight Pc P Absorption and Srlsupporting
confidence: 93%
“…The total dry weight of cotton reduced by 70.04 and 77.26% in the ND and JM cultivars, respectively, under low P stress, compared with PR conditions. These findings are consistent with the results of Xie et al (2021), who found that low P stress can significantly reduce the dry weight of cedar trees.…”
Section: Low P Stress Reduces Cotton Dry Matter Weight Pc P Absorption and Srlsupporting
confidence: 93%